The invisible workforce during the COVID-19 pandemic: Family carers at the frontline [version 1; peer review: 2 approved] - Dominique Phillips; Gillian Paul; Majella Fahy; Linda Dowling-Hetherington; Thilo Kroll; Breda Moloney; Clare Duffy; Gerard Fealy; Attracta Lafferty (HRB Open Research, 2020)
This is an open letter to acknowledge the essential and increasingly challenging role unpaid family carers are playing in the COVID-19 pandemic. The letter is written by members of the CAREWELL team, a HRB-funded project that aims to promote health and self-care behaviours among working family carers. Family carers provide care to family and friends in the community who need support due to old-age, disability and chronic illness. In many cases, family carers are supporting those who are considered most at risk in this pandemic meaning carers must reduce their own risk of infection in order to protect their dependent family members. The temporary reduction of some home care services, as well as school and creche closures, means that family carers are providing increased levels of care with little or no support. At a time when both worlds of work and care have been dramatically transformed, we wish to shed light on those who are currently balancing paid employment with a family caregiving role. We argue that there is much to be learned from the recent work restrictions that could benefit employees, including working family carers, beyond this pandemic. We also wish to build on the potential positives of a transformed society and encourage policy makers and employers to focus on what is currently being implemented, and to identify which measures could be used to create a bedrock of policies and practices that would offer robust and effective support to family carers. It is hoped that family carers will receive greater recognition for the significant role they play in society, providing essential care and alleviating the strain on health and social care systems, both during and post the COVID-19 pandemic.